2011
DOI: 10.1088/1367-2630/13/12/125014
|View full text |Cite
|
Sign up to set email alerts
|

The x-ray luminous galaxy cluster population at 0.9 <z≲ 1.6 as revealed by the XMM-NewtonDistant Cluster Project

Abstract: We present the largest sample of spectroscopically confirmed X-ray luminous high-redshift galaxy clusters to date comprising 22 systems in the range 0.9 < z < ∼ 1.6 as part of the XMM-Newton Distant Cluster Project (XDCP). All systems were initially selected as extended X-ray sources over 76.1 deg 2 of non-contiguous deep archival XMM-Newton coverage, of which 49.4 deg 2 are part of the core survey with a quantifiable selection function and 17.7 deg 2 are classified as 'gold' coverage as starting point for upc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(150 citation statements)
references
References 106 publications
8
142
0
Order By: Relevance
“…Among these are the XMM Deep Cluster Project (XDCP2; Fassbender et al 2011) that has so far spectroscopically confirmed 22 clusters at z > 0.8. The study of these high redshift objects is extremely important.…”
Section: Evolutionmentioning
confidence: 99%
“…Among these are the XMM Deep Cluster Project (XDCP2; Fassbender et al 2011) that has so far spectroscopically confirmed 22 clusters at z > 0.8. The study of these high redshift objects is extremely important.…”
Section: Evolutionmentioning
confidence: 99%
“…Several other projects are being conducted to detect galaxy clusters from the observations of the XMM-Newton, Chandra, and the X-ray Telescope A&A 558, A75 (2013) on board of the Swift satellite (e.g. Barkhouse et al 2006; Kolokotronis et al 2006;Finoguenov et al 2007Finoguenov et al , 2010Adami et al 2011;Fassbender et al 2011;Takey et al 2011;Mehrtens et al 2012;Clerc et al 2012;Tundo et al 2012;de Hoon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up z, H photometry was originally obtained with the near-IR, wide-field camera OMEGA2000 mounted at the prime focus of the 3.5 m telescope at Calar Alto, Spain. A redshift z ∼ 1.45 ± 0.15 was inferred from comparison between the average z − H colour of the reddest galaxies within 45 from the X-ray position of XMMU J0338.7+0030 and the synthetic z − H colours expected for a large suite of simple stellar population (SSP) models (see Fassbender et al 2011c). The synthetic photometry was computed using the spectro-photometric evolutionary synthesis model PÉGASE v2 (Fioc & Rocca-Volmerange 1997) in analogy with Pierini et al (2005) and Wilman et al (2008).…”
Section: Introductionmentioning
confidence: 99%